2015
DOI: 10.1371/journal.pone.0142733
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Multiple Non-EV71 and Non-CVA16 Enteroviruses Associated with Hand, Foot and Mouth Disease in Jinan, China, 2009—June 2013

Abstract: Hand, foot, and mouth disease (HFMD) is an infectious disease caused by human enterovirus 71 (EV71), coxsackievirus A16 (CVA16) and other enteroviruses. It is of interest that other enteroviruses associated with HFMD in Jinan have been rarely reported. The aim of the present study is to detect and characterize the circulating serotypes of non-EV71 and non-CVA16 enteroviruses associated with HFMD in Jinan city, Shandong province, China. A total of 400 specimens were collected from clinically diagnosed HFMD case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…Though EV71 was a major pathogen, other EVs, especially CVA6 and CVA10, are prevalent and have become the predominant causative agents. [12][13][14] In Jiangsu province, EV71 and CVA16 were the major etiologic agents of HFMD 20 from 2009 to 2012. For example, a previous study 21 showed that EV71 was the main pathogen causing HFMD in Suzhou, Jiangsu Province from April to July 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though EV71 was a major pathogen, other EVs, especially CVA6 and CVA10, are prevalent and have become the predominant causative agents. [12][13][14] In Jiangsu province, EV71 and CVA16 were the major etiologic agents of HFMD 20 from 2009 to 2012. For example, a previous study 21 showed that EV71 was the main pathogen causing HFMD in Suzhou, Jiangsu Province from April to July 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2008, other enteroviruses (EVs), such as CVA6 and CVA10, along with EV17 and CVA16, were also identified as the major pathogens in several HFMD outbreaks. [4][5][6][7][8][9][10][11][12][13][14] HFMD has been a major public health concern in China since the first case report 15 in Shanghai in 1982. In 2008, a huge outbreak of HFMD caused by EV71 in FuYang City, China, had a significant impact on the health of local infants and young children.…”
mentioning
confidence: 99%
“…Several studies on CV-A10 genotyping were based on 5′-UTR 10 , VP4 11 , or partial VP1 3 , 4 , 12 , 13 . However, VP1 plays a critical role in mediating binding receptor and the complete VP1 has been used widely to identify EV serotypes 14 18 as its coding region contains many important neutralizing antigenic sites.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, there were 4 young children reported with severe upper respiratory illness due to CV-A2 infections in Hong Kong, 2 of whom died [9]. In 2009–2013, CV-A2 was one of the most dominant types of the 12 circulating serotypes of EVs causing HFMD in Jinan, Shandong province [10]. In 2013, an epidemic of herpangina occurred in Shenzhen of Guangdong province due to CV-A2 infection.…”
Section: Introductionmentioning
confidence: 99%